"An Open Letter to Eugene V. Debs": Debs' Relationship to the U.S. Communists, Circa 1919–1924. Issue 2 (June 2015) - Devinatz, Victor G.
<x xml:space="preserve">Abstract</x> U.S. Communists have addressed why Eugene V. Debs remained a Socialist Party of America (SPA) member as opposed to joining the Communists when the SPA left‐wing split occurred in 1919. The literature on Debs, the SPA and U.S. Communism's history, however, fails to mention the Communist Party of America's Central Executive Committee writing a letter to Debs published in the April 25, 1920 issue of The Communist. This letter is significant because it is the first place where the Communists present their dualistic views on Debs after the SPA split. Becoming the standard interpretation in U.S. Communist historiography after his death, Debs is portrayed as a heroic militant, class‐conscious warrior who would have joined the Communists in 1919 had he received accurate information about the SPA. This claim, however, lacks support after examining the historical evidence. The article concludes with lessons that can be drawn from this discussion for the early twenty‐first century U.S. trade union movement.